Early Life HIV-1 Immunization: Providing a Window for Protection Before Sexual Debut - Permar, Sallie (AIDS Res Hum Retroviruses, 2018)
Limited success of current HIV-1 vaccines warrants new approaches. We discuss feasibility and potential benefits of early life HIV-1 immunization followed by vaccine boosts during childhood that may enable maturation of vaccine-induced broad anti-HIV-1 immunity over several years. By initiating this immunization approach in the very young, well before sexual debut, such a strategy may dramatically reduce the risk of HIV-1 infection.